Exploring the Capability to Backward Induct – An Experimental Study with Children and Young Adults - Jeannette Brosig-Koch; Timo Heinrich; Christoph Helbach (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
We investigate learning and the development of the capability to backward induct in children and young adults aged 6 to 23 under controlled laboratory conditions. The experimental design employs a modified version of the race game. As in the original game (see Burks et al., 2009, Dufwenberg et al., 2010, Gneezy et al., 2010, and Levitt et al., 2011), subjects need to apply backward induction in order to solve the games. We find that subjects' capability to backward induct improves with age, but that this process systematically diff ers across gender. Our repetition of the games provides insights into differences in learning between age groups and across gender. – – Diese Studie untersucht mit Hilfe von Laborexperimenten, wie sich die Fähigkeit, Rückwärtsinduktion zu betreiben, mit dem Alter entwickelt. Teilnehmer im Alter zwischen 6 und 23 Jahren spielen dazu eine modifizierte Version des 'Race Game' (vgl. auch Burks et al., 2009, Dufwenberg et al., 2010, Gneezy et al., 2010, Levitt et al., 2011), das durch Rückwärtsinduktion gelöst werden kann. Dies gelingt älteren Teilnehmern häufiger als jüngeren. Gleichzeitig deuten die Daten auf systematische Unterschiede dieser Entwicklung mit dem Alter zwischen Männern und Frauen hin. Durch die Wiederholung verschiedener Spielvarianten ergeben sich außerdem Einblicke in alters- und geschlechtsspezifische Lerneffekte.
Keywords: C72; J13; C91; 330; Backward induction; learning; age effects; experimental economics; children